Lactate - a signal coordinating cell and systemic function - Philp, A.; Macdonald, A. L.; Watt, P. W. (The Journal of Experimental Biology, 2005)
Since its first documented observation in exhausted animal muscle in the early 19th century, the role of lactate (lactic acid) has fascinated muscle physiologists and biochemists. Initial interpretation was that lactate appeared as a waste product and was responsible in some way for exhaustion during exercise. Recent evidence, and new lines of investigation, now place lactate as an active metabolite, capable of moving between cells, tissues and organs, where it may be oxidised as a fuel or reconverted to form pyruvate or glucose. The questions now to be asked concern the effects of lactate at the systemic and cellular level on metabolic processes. Does lactate act as a metabolic signal to specific tissues, becoming a metabolite pseudo-hormone? Does lactate have a role in whole-body coordination of sympathetic/parasympathetic nerve system control? And, finally, does lactate play a role in maintaining muscle excitability during intense muscle contraction?